Peripheral inflammation affects modulation of nociceptive synaptic transmission in the spinal cord induced by N-arachidonoylphosphatidylethanolamine - Nerandzic, Vladimir; Mrozkova, Petra; Adamek, Pavel; Spicarova, Diana; Nagy, Istvan; Palecek, Jiri (British journal of pharmacology, 2018)
BACKGROUND AND PURPOSE: Endocannabinoids play an important role in modulating spinal nociceptive signalling, crucial for the development of pain. The cannabinoid CB1 receptor and the TRPV1 cation channel are both activated by the endocannabinoid anandamide, a product of biosynthesis from the endogenous lipid precursor N-arachidonoylphosphatidylethanolamine (20:4-NAPE). Here, we report CB1 receptor- and TRPV1-mediated effects of 20:4-NAPE on spinal synaptic transmission in control and inflammatory conditions. EXPERIMENTAL APPROACH: Spontaneous (sEPSCs) and dorsal root stimulation-evoked (eEPSCs) excitatory postsynaptic currents from superficial dorsal horn neurons in rat spinal cord slices were assessed. Peripheral inflammation was induced by carrageenan. Anandamide concentration was assessed by mass spectrometry. KEY RESULTS: Application of 20:4-NAPE increased anandamide concentration in vitro. 20:4-NAPE (20 μM) decreased sEPSCs frequency and eEPSCs amplitude in control and inflammatory conditions. The inhibitory effect of 20:4-NAPE was sensitive to CB1 receptor antagonist PF514273 (0.2 μM) in both conditions, but to the TRPV1 antagonist SB366791 (10 μM) only after inflammation. After inflammation, 20:4-NAPE increased sEPSCs frequency in the presence of PF514273 and this increase was blocked by SB366791. CONCLUSIONS AND IMPLICATIONS: While 20:4-NAPE treatment inhibited the excitatory synaptic transmission in both naive and inflammatory conditions, peripheral inflammation altered the underlying mechanisms. Our data indicate that 20:4-NAPE application induced mainly CB1 receptor-mediated inhibitory effects in naive animals while TRPV1-mediated mechanisms were also involved after inflammation. Increasing anandamide levels for analgesic purposes by applying substrate for its local synthesis may be more effective than systemic anandamide application or inhibition of its degradation. LINKED ARTICLES: This article is part of a themed section on Recent Advances in Targeting Ion Channels to Treat Chronic Pain. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v175.12/issuetoc.
Keywords: Synaptic Transmission; Male; Rats, Wistar; Carrageenan; Inflammation; Spinal Cord; Structure-Activity Relationship; fosfatidylethanolaminy; vztah mezi dávkou a účinkem léčiva; mužské pohlaví; Mass Spectrometry; potkani Wistar; karagenan; nervový přenos; vztahy mezi strukturou a aktivitou; zánět; krysa rodu Rattus; Animals; mícha; zvířata; buňky zadních rohů míšních; Phosphatidylethanolamines; Rats; Posterior Horn Cells; hmotnostní spektrometrie; Dose-Response Relationship, Drug